TOLONG! AWEK AKU PONTIANAK - Lee, James; Pillai, Gayatri Su-Lin; Zahiril Adzim; Sazzy Falak; Liyana Jasmay; Sufian Mohamed; Rashidi Ishak; Yus Waisar; Nurul Wahab; Syanie; Jalaludin Hassan, Datuk; Harun Salim Bachik (Seri Kembangan, Selangor : Tayangan Unggul, 2011)
Sebuah filem komedi seram yang mengisahkan Bob berperwatakan lurus bendul dan Pian mula berkenalan dengan Maya dan Liyana. Mereka berempat menjadi kawan baik. Faizal, majikan kepada Bob dan Pian menawarkan Maya bekerja di syarikatnya untuk membongkar identiti Maya dan Liyana.
Title from container
Sound Department : Sergei Groshev ; Re-recording mixer : Warren Santiago, Dustin Riduan Shah ; Sound designer Special Effects by Eds Arippin ; Post-production coordinator (as Abd Samad Hassan)
Performers : Zahiril Adzim, Sazzy Falak, Liyana Jasmay, Sufian Mohamed, Rashidi Ishak, Yus Waisar, Nurul Wahab, Syanie, Datuk Jalaludin Hassan, Harun Salim Bachik
P13 - Under 13, audiences need supervision and guidance from parents or guardians when watching. Movies contain horror, scary, negative scenes or actions, suspense elements and surprising but not excessive; elusive storylines and elements that can disturb children's emotions.
DVD, MPEG 2, PAL, Surround 5.1
In Malay version with English subtitles
Keywords: Motion picture -- Malaysia; Comedy films -- Malaysia; Feature films